Militarisation of conservation, violence and local people: the case of Sikumi Forest Reserve in Zimbabwe - Mushonga, Tafadzwa (Department of Sociology, 2019)
Violence in protected areas has become more pronounced in the last decade due to the increasing use of military practices in conservation. This study examines the texture and nature of everyday militarisation and violence effected in protected areas different from national parks and wildlife conservation. It also examines the consequences of militarised conservation on people living in, or adjacent to, these protected areas. The analysis takes a case study and ethnographic approach. It is embedded in daily patrol activities of the state paramilitary unit responsible for conservation enforcement and in experiences, with the practice of militarisation, of people living around Sikumi Forest Reserve in Zimbabwe. The study demonstrates that the form and texture of militarisation in conservation are dependent on the type of protected area, and the nature of resources under protection. It is additionally dependent on the political-economic context, and the capacity, of the state authorities responsible for protected area management, to execute military practices. Thus, protected areas that are different from national parks and, or, managed by organisations without resources to implement militarised conservation policies, may paint a different picture of militarisation. They can enforce militarised policies and strategies but only in a symbolic manner towards halting armed poaching activities. These insights reflect an alternative pattern of militarisation, which this study frames as symbolic green militarisation. Symbolic green militarisation is developed to provide alternative thinking to the idea that use of paramilitary personnel, strategies and technologies transforms protected areas into war zones or deadly landscapes. The study presents evidence that while symbolic green militarisation may not result in high-level violence, it is sufficient to expose local people, who depend on protected areas for subsistence, to particular and diverse forms of direct and indirect violence. These forms of violence are often facilitated and perpetuated by factors beyond immediate conservation practice. The study broadly argues that, regardless of the texture and nature of militarisation, demonstration or use of any amount of force in protected areas has rather significant consequences for local people who need such spaces to support their development. Overall, the resurgence of fortress conservation coupled with the adoption of military practices represents hope deferred for local people.